The comparison of students’ long jump study programs - Andrii Yefremenko; Svitlana Рiatysotska; Viktor Pavlenko (Слобожанський науково-спортивний вісник, 2023)
Background and Study Aim: The modern educational process in physical education needs to form educational competencies for a limited time. It is necessary to use modern approaches. Purpose – to determine the effectiveness of holistic and differentiated methods of study the technique of long jumps by combat sports students.